Formation of Essential Ultrastructural Interface between Cultured Hippocampal Cells and Gold Mushroom-Shaped MEA- Toward “IN-CELL” Recordings from Vertebrate Neurons - Fendyur, Anna; Mazurski, Noa; Shappir, Joseph; Spira, Micha E. (Frontiers in Neuroengineering, 2011)
Using cultured Aplysia neurons we recently reported on the development of a novel approach in which an extracellular, non-invasive multi-electrode-array system provides multisite, attenuated, intracellular recordings of subthreshold synaptic potentials, and action potentials (APs), the so called “IN-CELL” recording configuration (to differentiate it from intracellular recordings). Because of its non-invasive nature, the configuration can be used for long term semi intracellular electrophysiological monitoring of APs and synaptic potentials. Three principals converge to generate the IN-CELL configuration: (a) engulfment of approximately 1 μm size gold mushroom-shaped microelectrodes (gMμE) by the neurons, (b) formation of high seal resistance between the cell’s plasma membrane and the engulfed gMμE, and (c), autonomous localized increased conductance of the membrane patch facing the gMμE. Using dissociated rat hippocampal cultures we report here that the necessary morphological and ultrastructural relationships to generate the IN-CELL recording configuration are formed between hippocampal cells and the gMμEs. Interestingly, even <1 μm thin branches expand and engulf the gMμE structures. Recordings of spontaneous electrical activity revealed fast ∼2 ms, 0.04–0.75 mV positive monophasic APs (FPMP). We propose that the FPMP are attenuated APs generated by neurons that engulf gMμEs. Computer simulations of analog electrical circuits depicting the cell–gMμE configuration point out the parameters that should be altered to improve the neuron–gMμE electrical coupling.